Prayer Leads to Advocacy: The Theological Logic in a Bishop's Statement on Comprehensive Immigration Reform - James W. Vining (Frontiers in Communication, 2022)
This article contributes to the scholarly discussions about the role of religion in social and political action rhetoric by revealing the complexities of rhetorical resources found in the logic of theology. To this end, I explored rhetorical functions of theology in Bishop Michael Burbidge's 2013 Statement on Comprehensive Immigration Reform. Close textual analysis of the text allows scholars to identify what I call the textual theology—a mediating level of theology between theological traditions and the rhetoric in a text. Analysis of the textual theology in the Bishop's statement provides insights as to how the more abstract levels of theology animate texts in the real world in ways that have implications that reach beyond the particular text.